PHENETIC ANALYSIS AND DISTRIBUTION OF CLAOXYLON IN THE LESSER SUNDA ISLANDS - Adhy Widya Setiawan; Tatik Chikmawati (Floribunda, 2020)
Phenetic Analysis and Distribution of Claoxylon in the Lesser Sunda Islands. Floribunda 6(5): 167–174.  — The genus Claoxylon A.Juss. in the Lesser Sunda Islands (LSI) was reviewed. Eleven species were recognized in Lesser Sunda Islands. Records of C. capillipes and C. fulvescens were extended to the Bali Island. Based on distribution of Claoxylon in LSI, Bali has the highest number of species (7 species), while Wetar shows the least number of species (only 1 species). A phenetic analysis was using Numerical Taxonomy and Multivariate Analysis System (NTSYS-pc) version 2.11a and distribution mapping using Quantum GIS version 2.4. Based on 14 morphological characters grouped Claoxylon species in LSI into three groups. All Claoxylon in LSI belong to section Indica and Affinia.